Improving referrals to a fracture liaison service: Screening for osteoporosis. (November 2022) - McDowell, Samantha L.; Freeman, Julie C.
Abstract: With the elderly population living longer and 'baby boomer's now reaching the age of 65, there is great concern regarding a lack of diagnosis and treatment of osteoporosis. Osteoporosis is a well-known problem, yet there continue to be gaps regarding screening and treatment. An orthopaedic practice in the Southeastern United States specializing in bone health has an internal Fracture Liaison Service (FLS) that was not being fully utilized by the providers. A quality improvement project was implemented following the recommended FLS guidelines to identify individuals that should receive referral to the FLS. Chart audits were completed to analyze both pre- and post-implementation phases. An alert button was introduced into the electronic health record to prompt orthopaedic surgeons to refer to the FLS clinic when individuals met the requirements of age and a first-time fragility fracture. Descriptive data showed 5% FLS referrals in 2019. After implementation of the alert button the FLS referrals for 2020 were 19%, providing a 14% overall improvement rate. Evidence supports using standardized screening processes and that referring to an FLS is best practice for improving the treatment of osteoporosis and for decreasing morbidity, mortality, and health care cost.